2021
DOI: 10.1038/s41598-021-90764-9
|View full text |Cite
|
Sign up to set email alerts
|

Viral-mediated transduction of auditory neurons with opsins for optical and hybrid activation

Abstract: Optical stimulation is a paradigm-shifting approach to modulating neural activity that has the potential to overcome the issue of current spread that occurs with electrical stimulation by providing focused stimuli. But optical stimulation either requires high power infrared light or genetic modification of neurons to make them responsive to lower power visible light. This work examines optical activation of auditory neurons following optogenetic modification via AAV injection in two species (mouse and guinea p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Unfortunately, such techniques do not achieve complete transfection of the nerve, leaving some neurons that do not express the opsin and are incapable of optogenetic and hybrid responses. Indeed, a previous study demonstrated that hybrid stimulation did not have any consistent effect on the spatial precision, although subthreshold optogenetic stimulation did reduce the electrical activation threshold [46]. Techniques to improve transfection rates of gene therapy are likely to benefit not only optogenetic stimulation but also hybrid stimulation.…”
Section: Limitations and Clinical Translationmentioning
confidence: 99%
“…Unfortunately, such techniques do not achieve complete transfection of the nerve, leaving some neurons that do not express the opsin and are incapable of optogenetic and hybrid responses. Indeed, a previous study demonstrated that hybrid stimulation did not have any consistent effect on the spatial precision, although subthreshold optogenetic stimulation did reduce the electrical activation threshold [46]. Techniques to improve transfection rates of gene therapy are likely to benefit not only optogenetic stimulation but also hybrid stimulation.…”
Section: Limitations and Clinical Translationmentioning
confidence: 99%
“…For example, the combination of electrical and infrared stimulation of the auditory nerve in deaf white cats reduced the required radiant (light) energy (Richter et al , 2014 ). Another study combining electrical and optogenetic stimulation in mice expressing a ChR2 variant showed that sub‐threshold optical stimulation was able to lower the threshold for subsequent electrical stimulation (Richardson et al , 2021 ).…”
Section: Future Strategies For Improved Hearing Restorationmentioning
confidence: 99%
“…As a new frontier of optogenetic based therapies emerges, we envisage a technique such as an opto-electrical hybrid stimulation could contribute to improved delivery of arti cial vision and serve as a pioneer for the intersection between gene therapy and bionics. The e cacy of hybrid stimulation has already been demonstrated in both the cochlea [24][25][26][27] and sciatic nerve 28 . In the cochlea, hybrid stimulation reduced the electrical stimulation current required, thus signi cantly reducing the spread of activation compared to electrical-only stimulation 27 .…”
Section: Introductionmentioning
confidence: 99%